Challenges Affecting the Implementation of Decentralisation in Public Basic Schools in Ghana - Kyeremeh, Alex; Kor, Jacob Aaworb-nang Maabobr (Advances in Social Sciences Research Journal, 2022)
Educational management is a major element that produces successful educational outcomes. Over the years decentralisation has become one major policy for effective and efficient educational management in public basic schools in Ghana. Decentralisation entails the transfer of administrative and fiscal authority to the grassroot where management decisions prickly taken for effective management. This study sought to investigate challenges mitigating the implementation of decentralisation in public basic schools in Ghana. Among some key challenges faced were inadequate logistics for key stakeholders to carry out their functions. Again, there are limited support for infrastructure from both local and governmental levels. There are inadequate and delay in supply of teaching and learning materials. Delay in decision on appointments, promotions and sanction of errant staff. Political interference by government appointees also affects implementation of effective decentralisation. Difficulty in monitoring and supervise some schools due to bad roads in deprived communities also have adverse effect on the implementation of decentralisation. It was recommended devolution policy to replace the existing decentralisation policy in public basic schools for the full benefit of decentralisation. This will make it possible for major decisions like appointments, promotions and disciplinary actions taken at grassroot level instead of the centre. Logistics and TLM must get to schools on time for effective management of school.